Attenuation of Redox Switching and Rectification in Azulenequinones/Hydroquinones after B and N Doping: A First‐Principles Investigation. Issue 1 (30th November 2020) - Haidar, El‐Abed; Tawfik, Sherif Abdulkader; Stampfl, Catherine; Hirao, Kimihiko; Yoshizawa, Kazunari; Nakajima, Takahito; Soliman, Kamal A.; El‐Nahas, Ahmed M.
Abstract: The redox switching of doped 1, 5‐azulenequinones/hydroquinones wired between gold electrodes is investigated using density functional theory and the nonequilibrium Green's function. Their electronic transport properties when separately doped with nitrogen and boron as well as co‐doping of these atoms are examined. The results illustrate a significant enhancement of the current at low bias voltage in some of the 12 doped studied systems, leading to "switching on" the transmission, where the greatest switching ratio is 18. These systems also exhibit a modest rectification in which the greatest rectification ratio is 4. The significance of the position of the doped atom and the functional group on the switching behavior is analyzed through the transmission spectra and molecular orbitals. The present study broadens knowledge of organic redox switching bringing in potential diverse options for future molecular electronic circuit components. Abstract : Redox switching and rectification of doped 1, 5‐azulenequinones/hydroquinones sandwiched between two gold electrodes are investigated using density functional theory and the nonequilibrium Green's function. A significant enhancement of the current at low bias voltage is observed in some of the studied systems. Position of the doped atom is analyzed through the transmission spectra and molecular orbitals.